2015
DOI: 10.1007/s00056-015-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy of jaw scans performed on alginate impressions or stone models

Abstract: Alginate impressions can be suitably digitized by structured-light scanning and offer considerably better dimensional accuracy than stone models. Apparently, however, both impression scans and stone-model scans can offer adequate precision for orthodontic purposes. The main issue of impression scans (which is incomplete representation of model surfaces) is being systematically explored in a follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…These results appear to be partially supported by previous findings: Santoro et al 16) measured a plaster model by hand using a digital caliper, and compared this to a digital model generated from an alginate impression using OrthoCAD (Cadent, Fairview, NJ, USA). His study reported that all tooth-size measurements from the digital model were smaller compared to the plaster model, which may be due to shrinkage of impression, expansion of gypsum 4) , or distorted digital data. Flügge et al 7) compared intraoral and extraoral scanning using the same scanner (iTero, Align Technologies, San Jose, CA, USA), and reported that intraoral scanning was less accurate than extraoral scanning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results appear to be partially supported by previous findings: Santoro et al 16) measured a plaster model by hand using a digital caliper, and compared this to a digital model generated from an alginate impression using OrthoCAD (Cadent, Fairview, NJ, USA). His study reported that all tooth-size measurements from the digital model were smaller compared to the plaster model, which may be due to shrinkage of impression, expansion of gypsum 4) , or distorted digital data. Flügge et al 7) compared intraoral and extraoral scanning using the same scanner (iTero, Align Technologies, San Jose, CA, USA), and reported that intraoral scanning was less accurate than extraoral scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Digital three-dimensional (3D) models are created by scanning impression and plaster models using desktop scanners, or otherwise by cone-beam computed tomography. These methods have been widely accepted in clinical orthodontics, and are advantageous due to the compact storage space, their potential to expand applications for treatment planning, and their easy customization 4,5) . The use of commercial intraoral scanners to capture information on dental arches has increased in recent years, and is an attractive method for orthodontist.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is not the topic of the study, it is at least obligatory to mention them briefly. Alginates can be used primarily to take impressions even in contact with other structures such as bone structures, both in the maxillofacial region and in other regions in orthopedics [22]. This material must be completely removed because it can go against an inflammatory reaction from the tissues [23].…”
Section: Methodsmentioning
confidence: 99%
“…With optical scanners, it is possible to create digital models by directly scanning the patient's teeth or indirectly scanning the cast or impression. [7][8][9][10] Digital casts allow prosthodontists to perform diagnosis, treatment planning, and fabrication of the final restoration virtually by computer aided appliance manufacturing. 11,12 Also, they allow digital casts to completely replace conventional casts in case when a physical representation of the cast is needed for legal purposes or prosthesis design.…”
Section: Introductionmentioning
confidence: 99%